2023
DOI: 10.1002/ppul.26315
|View full text |Cite
|
Sign up to set email alerts
|

How has the SARS‐CoV‐2 pandemic changed the epidemiology and management of acute bronchiolitis?

Abstract: Objective SARS‐COV‐2 pandemic profoundly impacted acute bronchiolitis epidemiology worldwide, especially respiratory syncytial virus (RSV) diffusion and the burden of disease, with remarkable implications on the management of health resources. We aimed to study the epidemiology and clinical course of bronchiolitis in the past 5 years in our region and to assess the trends that occurred during and after the SARS‐COV‐2 pandemic. Methods We conducted an observational study including all children aged 0–2 years wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Recent literature has shown a higher incidence of bronchiolitis in the post‐pandemic period, but the reports regarding disease severity are conflicting 7–9 . A previous study by our group showed that in our setting the number of hospitalized bronchiolitis and the need for respiratory support increased over the last 5 years (2017–2022), probably due to a higher prevalence of RSV infections, although no significant changes were seen regarding the need for mechanical ventilation (MV) and intensive care admissions 10 …”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…Recent literature has shown a higher incidence of bronchiolitis in the post‐pandemic period, but the reports regarding disease severity are conflicting 7–9 . A previous study by our group showed that in our setting the number of hospitalized bronchiolitis and the need for respiratory support increased over the last 5 years (2017–2022), probably due to a higher prevalence of RSV infections, although no significant changes were seen regarding the need for mechanical ventilation (MV) and intensive care admissions 10 …”
Section: Introductionmentioning
confidence: 70%
“…The non‐pharmaceutical interventions imposed by the pandemic initially determined a dramatic reduction in incidence rates of all infections, including bronchiolitis, 15–17 followed by a significant resurgence associated with epidemiological changes, including out‐of‐season outbreaks 6,10,18 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The epidemiology of acute bronchiolitis has been highly modi ed after the covid with one of the most severe epidemics in 2022-2023 [10,11,28]. The widespread of Nirsevimab in the coming years (RSVspeci c antibody) might also change the characteristics of infants with severe bronchiolitis [29].…”
Section: Discussionmentioning
confidence: 99%